ENGLISH POSTER AS A MINITEXT IN A PERIOD OF THE AMERICAN CIVIL WAR (1861-1865) - Чорнобай, Ю. В. (Studia Philologica, 2019)
In spite of the fact that researchers pay much attention to the semantic side of minitext, still there is no established understanding of many of its semantic, lexical and pragmatic components. This article reveals the purpose of the military poster as a minitext, its communicative and pragmatic orientation, as well as possible definition of poster and typology for verbal and non-verbal components. Additionally, the findings indicate the characteristic features of poster: accuracy, shortness (maximum size of 2,000 characters and minimum, one sentence), completeness, visual and verbal components, specific punctuation and vocabulary. An important structural element of the poster is paralinguistic means (mainly, spatial placement of the verbal and visual components, and the font and style choosing). The verbal and non-verbal combination carries emotionality and effectiveness in the information transmitting, as well as motivates readers to react according to the poster`s content. The article suggests that poster as a type of a minitext is an effective visual channel of communication as it possesses a considerable number of paralinguistic expressive means. The article demonstrates that Posters of Amirican Civil War (1861–1865) can be divided into presidential elections, raising for war, recruiting soldier into the army, the enemy demonstration to the country and the world. Posters carry informative or humorous intention and are full of different linguostylistic and paralinguistic expressive means. Additionally, the article reveals the characteristic peculiarities of posters of South and North and gives some examples of verbal and non-verbal component domination in posters. It describes specific peculiarities of using of certain phrase combinations, colours, specific punctuation, capitalization, different style and font to increase the effect of the poster content on readers.